(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article is devoted to relevant problems of modern epistemology.Problems of epistemology were considered in the context of cultural, social, humanitarian reflection. Problems were analyzed in regards to relevant theoretical, methodological problems in the sphere of knowledge and epistemological content of modern philosophy. Patterns of development of modern domestic epistemology are shown. The basic tendencies of development of social epistemology were found. The variety of concepts and approaches in the field of epistemological research and evaluation was defined. Key words: science, epistemology, culture, discourse, knowledge, methodology, language, rationalism, thinking, mentality.